Biogenic Amines in Raw and Processed Seafood - Visciano, Pierina; Schirone, Maria; Tofalo, Rosanna; Suzzi, Giovanna (Frontiers in Microbiology, 2012)
The presence of biogenic amines in raw and processed seafood, associated with either time/temperature conditions or food technologies is discussed in the present paper from a safety and prevention point of view. In particular, storage temperature, handling practices, presence of microbial populations with decarboxylase activity and availability of free amino acids are considered the most important factors affecting the production of biogenic amines in raw seafood. On the other hand, some food technological treatments such as salting, ripening, fermentation or marination can increase the levels of biogenic amines in processed seafood. The consumption of high amount of biogenic amines, above all histamine, can result in food borne poisoning which is a worldwide problem. The European Regulation established as maximum limits for histamine, in fishery products from fish species associated with high histidine amounts, values ranging from 100 to 200 mg/kg, while for products which have undergone enzyme maturation treatment in brine, the aforementioned limits rise to 200 and 400 mg/kg. Preventive measures and emerging methods aiming at controlling the production of biogenic amines are also reported for potential application in seafood industries.